2011
DOI: 10.1021/ol103061g
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Dihydroxylations of Enynes with a Trisubstituted C═C Bond. An Unprecedented Route to γ-Lactone Building Blocks with a Quaternary Stereocenter

Abstract: En route to a comprehensive set of hydroxylactone building blocks (4R,5R)-, (4R,5S)-, (4S,5R)-, and (4S,5S)-5a, Sharpless asymmetric dihydroxylations of allylic chlorides (E)- and (Z)-9 were performed. They delivered the four stereoisomers of diol 10 with up to 92% ee and absolute configurations, which were proven to be in accordance with the Sharpless mnemonic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…This method may not be suitable for the synthesis of (+)-gregatin E ( 3a ) bearing an additional hydroxy group in the side chain. In this paper, we would like to report the first total synthesis of (+)-gregatin E ( 3a ) and a new total synthesis of (+)-gregatin B based on our carbonylation chemistry and Pd- or Cu-mediated coupling reactions …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This method may not be suitable for the synthesis of (+)-gregatin E ( 3a ) bearing an additional hydroxy group in the side chain. In this paper, we would like to report the first total synthesis of (+)-gregatin E ( 3a ) and a new total synthesis of (+)-gregatin B based on our carbonylation chemistry and Pd- or Cu-mediated coupling reactions …”
mentioning
confidence: 99%
“…An inseparable mixture of (±)- 18a and (±)- 18b (1:1) was obtained in 41% yield along with a mixture of unidentified compounds. The yield was improved (82%) using the CuTC-mediated coupling reaction . Unfortunately, fluoride-mediated desilylation (TBAF, HF–pyridine, and HF–Et 3 N) of the mixture of (±)- 18a and (±)- 18b failed.…”
mentioning
confidence: 99%
“…Most orthoesters stem from alcoholyses of imidoester hydrochlorides . Hence, (2 S ,3 R )- 8 was to be made by a Pinner cyclization of the known dihydroxynitrile (3 R ,4 S )- 9 and a subsequent methanolysis.…”
mentioning
confidence: 99%
“…Oxidation with Pr 4 N ⊕ RuO 4 ⊖ /NMO was accompanied by the loss of methanol and afforded the desired furanone ( S )- 7 . In anticipation of the need of an HPLC determination of the enantiopurity of our gregatin-to-be, we prepared the enantiomeric furanone ( R )- 7 , too (Scheme , lower half): by subjecting dihydroxynitrile (3 R ,4 R )- 9 a diastereomer of the previous starting material (3 R ,4 S )- 9 to the same sequence of steps, which had led to ( S )- 7 .…”
mentioning
confidence: 99%
“…Consequently, we set out to explore in depth the potential controlling elements of dihydroxylations of 1,2-disubstituted cis -enynes (Table ). Prior researchers have shown that tri-substituted cis -alkenes proved to be the most effective substrates for providing moderate to high enantioselectivity . Brimble and co-workers have shown that 1,2-disubstituted cis -olefins are generally poor substrates for Sharpless-type dihydroxylation reactions .…”
Section: Resultsmentioning
confidence: 99%